ORFV: A Novel Oncolytic and Immune Stimulating Parapoxvirus Therapeutic - Rintoul, Julia L (Nature Publishing Group, 2012)
Replicating viruses for the treatment of cancer have a number of advantages over traditional therapeutic modalities. They are highly targeted, self-amplifying, and have the added potential to act as both gene-therapy delivery vehicles and oncolytic agents. Parapoxvirus ovis or Orf virus (ORFV) is the prototypic species of the Parapoxvirus genus, causing a benign disease in its natural ungulate host. ORFV possesses a number of unique properties that make it an ideal viral backbone for the development of a cancer therapeutic: it is safe in humans, has the ability to cause repeat infections even in the presence of antibody, and it induces a potent T(h)-1-dominated immune response. Here, we show that live replicating ORFV induces an antitumor immune response in multiple syngeneic mouse models of cancer that is mediated largely by the potent activation of both cytokine-secreting, and tumoricidal natural killer (NK) cells. We have also highlighted the clinical potential of the virus by demonstration of human cancer cell oncolysis including efficacy in an A549 xenograft model of cancer.